Correlation Between Perception of Caring Behavior and Daily Living Activity Independence of Chronic Disease Patients in Bendan Hospital Pekalongan City - Sri Mumpuni Yuniarsih; Rokhaeni Eva Kuswandari; Rahajeng Win Martani (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
Chronic disease progresses slowly, takes a long time and requires medical treatment. Caring nurses are very important in providing nursing care to chronic diseases patients, which has an impact on independence of the patient's daily living activities. The aimed to determine correlation between percepstion of caring behavior and daily living activity independence of chronic disease patients in Bendan Hospital Pekalongan City.  This research design used survai analytic with cross sectional approach. Samples were  chronic disease patients who were hospitalized in Bendan Hospital in Pekalongan City  as many as 52 people by accidental sampling. The research instrument used questionare.  Data were analyzed used chi square. There was correlation between perception of caring behavior and daily living activity independence of chronic disease patients in Bendan Hospital Pekalongan City with r value 0,005. Nurses should improve caring behavior in chronic disease patients so that patients are compliant in undergoing treatment